2018
DOI: 10.1111/joor.12709
|View full text |Cite
|
Sign up to set email alerts
|

Biomechanical effect of mandibular advancement device with different protrusion positions for treatment of obstructive sleep apnoea on tooth and facial bone: A finite element study

Abstract: Mandibular advancement at 70% of maximum protrusion induces risks of tooth root resorption and bone resorption. The mandibular second molars were subjected to the highest stresses. Stress on the teeth and facial bones was the lowest at 40% of maximum mandibular advancement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 37 publications
1
19
0
Order By: Relevance
“…Finite element (FE) analysis has been widely used to simulate different behaviors in dentofacial orthopedics and dental biomechanics (Ammar, Ngan, Crout, Mucino, & Mukdadi, ; Borcic et al, ; Cattaneo, Dalstra, & Melsen, ; Chang, Shin, & Baek, ; Field et al, ; Geramy & Morgano, ; Hsu, Chen, Chen, Huang, & Chang, ; Kibi et al, ; Lee, Choi, Lee, Ahn, & Noh, ; Liang, Rong, Lin, & Xud, ; Liu, Chang, Wong, & Liu, ; Rudolph, Willes, & Sameshima, ; Singh, Mogra, Shetty, Shetty, & Philip, ; Soares et al, ; Toms & Eberhardt, ; Vukicevic, Zelic, Jovicic, Djuric, & Filipovic, ; Yu, Baik, Sung, Kim, & Cho, ; Zhang, Cui, Lu, & Wang, ), because of many problematic issues in clinical testing, such as subject discomfort and limit of accessible areas. In the study conducted by Lee et al (), FE analysis was performed to investigate the mechanical effect of different protrusion positions of a mandibular advancement device (MAD) on teeth and facial bones, since the MAD‐induced stress and strain have not been measured directly from living structures. Ammar et al () used the FE jawbone model to simulate canine retraction with mini‐screw anchorage and compared stresses on the mini‐screw and fracture failure of tangential orthodontic forces.…”
Section: Introductionmentioning
confidence: 99%
“…Finite element (FE) analysis has been widely used to simulate different behaviors in dentofacial orthopedics and dental biomechanics (Ammar, Ngan, Crout, Mucino, & Mukdadi, ; Borcic et al, ; Cattaneo, Dalstra, & Melsen, ; Chang, Shin, & Baek, ; Field et al, ; Geramy & Morgano, ; Hsu, Chen, Chen, Huang, & Chang, ; Kibi et al, ; Lee, Choi, Lee, Ahn, & Noh, ; Liang, Rong, Lin, & Xud, ; Liu, Chang, Wong, & Liu, ; Rudolph, Willes, & Sameshima, ; Singh, Mogra, Shetty, Shetty, & Philip, ; Soares et al, ; Toms & Eberhardt, ; Vukicevic, Zelic, Jovicic, Djuric, & Filipovic, ; Yu, Baik, Sung, Kim, & Cho, ; Zhang, Cui, Lu, & Wang, ), because of many problematic issues in clinical testing, such as subject discomfort and limit of accessible areas. In the study conducted by Lee et al (), FE analysis was performed to investigate the mechanical effect of different protrusion positions of a mandibular advancement device (MAD) on teeth and facial bones, since the MAD‐induced stress and strain have not been measured directly from living structures. Ammar et al () used the FE jawbone model to simulate canine retraction with mini‐screw anchorage and compared stresses on the mini‐screw and fracture failure of tangential orthodontic forces.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the mandible moves antero-posteriorly when a MAD is applied, so the restorative force is directly transmitted to the anterior teeth. However, recent FEM studies [ 23 , 34 ] showed that load concentration induced by MADs was greater on the posterior teeth than on the anteriors; therefore, it is necessary to evaluate force distribution on the overall dentition as well as on the anterior teeth.…”
Section: Discussionmentioning
confidence: 99%
“…Our results also highlighted that attention should be paid to the transverse dimension of the posterior teeth during the long-term use of MADs, as well as the anteroposterior movements of the incisors. Previously, Lee et al [ 23 ] showed the highest force value in the mandibular second molar; therefore, it is likely to be inclined lingually. In contrast, in our study, the mandibular second molar indicated had the lowest force value.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations